Designing and implementing a model-in-the-loop simulator for validating vehicle control software in a series electric hybrid bus (Scientific Journal of Research Studies in Future Management, 2023)
Today, the scope and variety of changes that are brought to today's organizations are so great that they have no choice but to adapt and respond to these changes and organizational factors. Also, in order to increase the efficiency and effectiveness of the organization and to ensure the provision of good and quality goods and services to customers and to gain their satisfaction, managers should manage their knowledge about customers. The present study examines the impact of organizational factors and customer motivation on the business performance of Ekhtaz Novin Bank. The research method used is descriptive, survey and correlation type. Also, the statistical population of the current research includes senior managers, marketing managers, employees and relevant experts in Ekhtaz Novin Bank. The sample size was determined using Cochran's formula of 207 people and the sampling method of the present study is simple random sampling. Research data was collected by library and field method and questionnaire was used as the tool. The reliability of the questionnaires has been confirmed using the Cronbach's alpha method of 0.766, and the validity of the instrument has been confirmed using the content method. Research information was analyzed with the help of Lisrel software and using statistical, descriptive and inferential tests. The results of this research indicate that the effect of organizational factors (innovation in services, risk tolerance, human resources, financial resources, structure) organizational and trust) is not significant on the business performance of New Economy Bank, moreover, the results show that the effect of information structure variables and customer needs on the business performance of New Economy Bank is not significant.